Myths in Education, Learning and Teaching 2015
DOI: 10.1057/9781137476982_9
|View full text |Cite
|
Sign up to set email alerts
|

Digital Literacy in Higher Education: The Rhetoric and the Reality

Abstract: This chapter examines empirical data to address the rhetoric of the digital native as a competent and digitally literate learner. The chapter also questions the reality of the notion that a digital delivery platform is easy to navigate and facilitates positive learning experiences. Data from surveys of students studying both on-campus and via distance education (or online) at the University of Southern Queensland (USQ), a regional Australian university, provides useful insights into the literacies of digital n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 26 publications
1
18
0
4
Order By: Relevance
“…Differences between generations are often said to impact on individuals’ engagement with technology (Helsper & Eynon, ), yet, generalising on age grounds is ‘problematic’ (Burton et al ., , p. 4). Nevertheless, much has already been rehearsed in the literature around those born after 1980 and the contention that they have grown up immersed in, surrounded by and comfortable with, technology (Bennett & Maton, ; Helsper & Eynon, ; Oblinger, ; Oblinger & Oblinger, ; Prensky, ; Prensky & Berry, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Differences between generations are often said to impact on individuals’ engagement with technology (Helsper & Eynon, ), yet, generalising on age grounds is ‘problematic’ (Burton et al ., , p. 4). Nevertheless, much has already been rehearsed in the literature around those born after 1980 and the contention that they have grown up immersed in, surrounded by and comfortable with, technology (Bennett & Maton, ; Helsper & Eynon, ; Oblinger, ; Oblinger & Oblinger, ; Prensky, ; Prensky & Berry, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Academics may possess assumptions that technology is quick, easy to use, effortlessly accessible and appropriate for all learning activities. Further, that students' technological experiences are homogeneous, accompanied by sophisticated knowledge of information technologies (Burton et al, 2015). Assumptions like this can further disadvantage students, placing them at risk of lagging behind in their studies as they make their transitions to online study navigating often unfamiliar and inconsistent learning management systems.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…Many institutions look to online learning as a panacea for increasing costs and growing student demands for convenient learning opportunities. Burton, Summers, Lawrence, Noble and Gibbings (2015) argue that, although perceived as digital natives, many students are inexperienced with online pedagogies and are unskilled and unprepared for navigating often inconsistent online learning management systems. There is also uncertainty about whether students who are technologically proficient and benefitting from state-of-the-art, ubiquitous technology know how to strategically employ technology-based tools to optimise their learning experiences (Burton et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This is not the case (Ng, 2012). There is growing recognition that technology use does not necessarily equate to technology understanding and may not contribute to transferable digital literacy skills (Burton, Summers, Lawrence, Noble & Gibbings, 2015;McLachlan, Craig & Coldwell-Neilson, 2016). Further, it has been demonstrated that, as a concept, the phrase digital natives is unhelpful when making assumptions around digital capabilities particularly of students (White & Le Cornu, 2017).…”
Section: Why Is Digital Literacy Important?mentioning
confidence: 99%